Pengembangan Media Pembelajaran Matematika Berbasis Visual Basic Untuk Siswa Kelas VIII SMP - Nurdin Arsyad; Nasrullah; Adinda Rezeky Anggriani (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2021)
The purposes of this research are to develop mathematical learning media based on visual basics and describe the quality of the media based on aspects of validity, practicality, and effectiveness. This type of research is development research with the ADDIE model which includes 5 stages: analysis, design, development, implementation, and evaluation. The instruments used in this research are the form of media assessment sheets by material experts, media experts, and teachers to measure validity; response questionnaires for the media and observation sheets for the learning implementation to measure practicality; and learning outcomes tests to measure the effectiveness of the media. Respondents for theproduct trial are students of class VIII SMP which consists of 6 students. The results showed that theassessment by material experts, media experts, and teacher obtained very good criteria so that the media was declared valid. The results of the response questionnaire analysis of teacher and students to the media obtained very good criteria. The results of observations of the implementation of learning showed a very good classification. The percentage of classical completeness from student learning outcomes tests reached 83,3% so the media was declared effective.